Effects of Framing Nicotine Reduction in Cigarettes on Anticipated Tobacco Product Use Intentions and Risk Perceptions Among US Adult Smokers. (23rd December 2019) - Popova, Lucy; Owusu, Daniel; Nyman, Amy L; Weaver, Scott R; Yang, Bo; Huang, Jidong; Ashley, David L
Abstract: Introduction: In 2017, the US Food and Drug Administration (FDA) proposed lowering the amount of nicotine in combusted cigarettes to minimally addictive levels. If used, to encourage cessation and maximize the benefits of this action, the FDA needs to determine the most effective way to communicate to the public the practical impact of this nicotine tobacco product standard. Methods: Data were collected in 2018 from a nationally representative, online probability sample of 1198 adult smokers (aged ≥18 years old) in the United States. Smokers were randomly assigned one of five versions of the question regarding what they would most likely do if nicotine in cigarettes was reduced (nicotine levels were reduced by 95%; the government reduced nicotine levels by 95%; cigarettes were no longer addictive; cigarettes no longer relieved cravings; cigarettes were changed so that you would be able to quit more easily). Effects of framing on anticipated tobacco use intentions and perceived risk of very low nicotine cigarettes (VLNCs) were evaluated with multinomial logistic regressions. Results: Framing the nicotine tobacco product standard as cigarettes no longer relieved cravings resulted in the highest proportion of smokers reporting they intend to quit in response to this standard (43.9%), lowest proportions reporting anticipated intentions to continue using combusted tobacco products (45.3%), and lowest proportion believing that VLNCs are less harmful than regular cigarettes (26%). Conclusions: Different frames of nicotine reduction in cigarettes differentially affected smokers' anticipated tobacco use intentions and perceived risk of VLNCs. Presenting reduction as making cigarettes unable to relieve cravings might be particularly effective at motivating cessation.